(3GdChd ef GdMceI GdeJYGdjI aj GdCSaGQ GdYbdjIs - (3GdTjQGRj, GdbhGej, GdeqdG, UOQ GdOjf, eMeO Hf EHQGgje Hf jMji, J (B1059 (3g`s ((3eMeO Ydj Hf eMeO fUjQ GdgRGQLjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3ajbhd GdabjQ Edi QMeI QHg GdZfj GdeTJgQ HUOQ GdOjf GdTjQGRj (B: (3Ef GdSYGOI jXf HgG Cf GdahR HGdOQLGJ GdMSjI hGdhUhd Edi (B...s
(3BNQgG (B:s
... (3GJbhG aQGSI GdeDef aEfg jfXQ HfhQ Gddg , hjSei Pdc faKG aj GdQhY , hVQH BNQ (B.... (3hGdGSJOdGd HGdCTcGd Ydi GdCMhGd (B. (3Je GdeLdO GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B5/303s
(3GdPQjYI (B2 - 36 (241)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs